The Influence of Brand Awareness, Brand Trust, and Sales Promotion on Le Minerale Bottled Water (AMDK) Purchasing Decisions in DKI Jakarta - Izataki, Arina; Hardini, Resti; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the Influence of Brand Awareness, Brand Trust, and Sales Promotion on Le Minerale Bottled Drinking Water (AMDK) Purchasing Decisions in DKI Jakarta. This sample and research was as many as 100 respondents who made purchasing decisions in DKI Jakarta. This study used primary data with a data collection method through questionnaires distributed to 100 respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) program version 23.0. From the results of the t-test, this study shows that Brand Awareness (X1) has a positive and significant influence on Purchasing Decisions, this can be seen from the results of the t-test where (t-value of 6.694 > 1.660 t-table) and its significance (0.000 < 0.05). Brand Trust (X2) has a positive and significant influence on Purchasing Decisions, this can be seen from the results of the t-test where (t-value 2.931 > 1.660 t-table) and its significance (0.004 < 0.05). Sales Promotion (X3) has a positive and significant influence on Purchasing Decisions, this can be seen from the results of the t-test where (t-value 2.115 > 1.660 t-table) and its significance (0.037 < 0.05). That way it can be concluded that Brand Awareness, Brand Trust, and Sales Promotion have a positive and significant effect on Purchasing Decisions.